Content of Nitric Oxide Final Product in Cartilage and Blood Serum of Rats at Low Temperature Modeling of Destructive and Dystrophic Process in Knee Joint - Vvedensky, B. P.; Tynynyka, L. N.; Kovalev, G. A.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2011)
In the mechanism of cartilage tissue degradation the nitric oxide has been found to play an important role. There has been examined the content of NO (nitrite) final metabolic product in cartilage tissue of knee joint and blood serum of rats during low temperature modeling of destructive-dystrophic process (DDP) of knee joint, caused by cryoinjury. It has been shown that its content increases in aged animals, likely testifying to an accumulation of collagen glycolysated products, suppression by NO of matrix polyglycans, leading to impaired mechanical properties of cartilage tissue. At low temperature modeling of DDP the content of NO final product in cartilage tissue and blood serum in experimental animals was 4 times increased if compared with intact ones. The examined index did not virtually change for 7 days in cartilage tissue of rats, meanwhile under the analogous conditions it increased in blood serum, testifying to the development of DDP in cartilage tissue of animal knee joint.